Influence of Atmospheric Stability on the Size Distribution of the Vertical Dust Flux Measured in Eroding Conditions Over a Flat Bare Sandy Field. Issue 4 (18th February 2020) - Khalfallah, B.; Bouet, C.; Labiadh, M.T.; Alfaro, S.C.; Bergametti, G.; Marticorena, B.; Lafon, S.; Chevaillier, S.; Féron, A.; Hease, P.; Henry des Tureaux, T.; Sekrafi, S.; et al.
Abstract: In spite of their importance for the modeling of the atmospheric cycle of mineral dust, measurements of the intensity and size distribution of the dust emission flux produced by wind erosion in natural conditions remain rare. During the WIND‐O‐V's (WIND erOsion in presence of sparse Vegetation) 2017 experiment, eight major erosion events having occurred on a sandy flat field of southern Tunisia were documented. Consistent with the small size (90 μm) of the erodible sand grains and the low aerodynamic roughness length ( Z 0  < 0.079 cm), the threshold for wind erosion was low ( u * t = 22 cm/s). The classical gradient method was applied to assess the size‐resolved vertical dust flux, and the stability of the atmosphere quantified by the means of the Richardson number ( Ri ) as well as of its shear stress ( u * ) and thermal gradient ( ∂θ / ∂z ) components. The vertical dust flux increased with u * following a power law but the number size distribution of the dust flux was found to be significantly richer in submicron particles in thermally unstable than in stable periods. This challenges the usual assumption that, independently of their size, the particles smaller than 10 μm follow equally the movements of the air masses in which they are embedded and that the thermal stratification of the surface layer does not affect the size distribution of the surface flux when measured a few meters above the ground. Finally, we propose a simple empirical method for taking this influence of the thermal instability into account. Key Points: The size‐resolved dust flux was measured during eight erosion events by the gradient method The size distribution of the dust flux depends on the surface layer stability conditions The vertical dust flux is enriched in submicron particles in thermally unstable conditions